2023
DOI: 10.1186/s12957-023-02957-3
|View full text |Cite
|
Sign up to set email alerts
|

Regional anesthesia did not improve postoperative long-term survival of tumor patients: a systematic review and meta-analysis of randomized controlled trials

Abstract: Objective Experimental research and clinical trials have reported a positive effect of regional anesthesia (RA) on prognosis of cancers. We systematically reviewed the efficacy of RA on recurrence-free survival (RFS) and overall survival (OS) after oncology surgeries. Methods PubMed, Cochrane library, and Embase were searched from inception to June 20, 2022 for RCTs in which any form of RA was initiated perioperatively. Time-to-event data (hazard r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…The serum of the patients under regional anesthesia was associated with higher human donor natural killer cell cytotoxicity levels [ 22 ]. However, previous systematic reviews and meta-analyses failed to establish the clinical significance of regional anesthesia in oncological outcomes [ 10 , 23 ]. Herein, 3 of 9 prospective studies examined the effect of the paravertebral block on long-term outcomes (2 studies were excluded from the outcome analysis owing to the limited sample sizes).…”
Section: Discussionmentioning
confidence: 99%
“…The serum of the patients under regional anesthesia was associated with higher human donor natural killer cell cytotoxicity levels [ 22 ]. However, previous systematic reviews and meta-analyses failed to establish the clinical significance of regional anesthesia in oncological outcomes [ 10 , 23 ]. Herein, 3 of 9 prospective studies examined the effect of the paravertebral block on long-term outcomes (2 studies were excluded from the outcome analysis owing to the limited sample sizes).…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent meta-analysis of 15 randomized clinical trials with 5,981 patients showed that when compared to general anesthesia, the regional anesthesia increased neither overall survival, nor recurrence-free days (35). It can be explai ned by the heterogeneity of patients involved (possible differences in SNP profi les of patients (36)), variations in anesthetic protocols, duration of administration and type of local anesthetic used, as well as by small cohorts of patients, and a small number of RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…A témáról a legújabb és egyben a legkomplexebb metaanalízist Li és mtsai végezték [22]. A 2023-ben megjelent tanulmányukba 15, randomizált klinikai vizsgálatot vontak be.…”
Section: Humán Vizsgálatokban Az áLtalános Anesztézia Kiegészítése Re...unclassified